Plane Closed Trajectories on Certain Manifolds with Rotation Metric - Romanov, S. S.; Романов, С. С.; Романов, С. С. (Institute of Mathematics, NAS of Ukraine, 2004)
Trajectories on spherical and toroidal manifolds are studied by methods of infinitesimal and global geometry.